The impact of multidimensional disadvantage over childhood on developmental outcomes in Australia. (29th May 2018) - Goldfeld, Sharon; O'Connor, Meredith; Chong, Shiau; Gray, Sarah; O'Connor, Elodie; Woolfenden, Sue; Redmond, Gerry; Williams, Katrina; Mensah, Fiona; Kvalsvig, Amanda; Badland, Hannah
Abstract: Background: Understanding the relationship between different aspects of disadvantage over time and domains of child development will facilitate the formulation of more precise policy responses. We examined the association between exposure to aspects of disadvantage over the childhood period (from 0–9 years) and child development at 10–11 years. Methods: We used data from the nationally representative birth cohort of the Longitudinal Study of Australian Children ( n = 4979). Generalized linear models with log-Poisson link were used to estimate the association between previously derived disadvantage trajectories (in each of four lenses of sociodemographic, geographic environments, health conditions and risk factors, and a composite of these) and risk of poor child developmental outcomes. Population-attributable fractions were calculated to quantify the potential benefit of providing all children with optimal conditions for each developmental outcome. Results: Trajectories of disadvantage were associated with developmental outcomes: children in the most disadvantaged composite trajectory had seven times higher risk of poor outcomes on two or more developmental domains, compared with those most advantaged. Trajectories of disadvantage in different lenses were varyingly associated with the child development domains of socio-emotional adjustment, physical functioning and learning competencies. Exposure to the most advantaged trajectory across all lenses could reduce poor developmental outcomes by as much as 70%. Conclusions: Exposure to disadvantage over time is associated with adverse child development outcomes. Developmental outcomes varied with the aspects of disadvantage experienced, highlighting potential targets for more precise policy responses. The findings provide evidence to stimulate advocacy and action to reduce child inequities.